Method for testing grafting rate of silane grafted polyolefin for photovoltaic packaging adhesive film

Through the TGA ash conversion method, the problem of difficult to test the grafting rate of silane-grafted polyolefins in the prior art is solved, and efficient and accurate measurement of the grafting rate of silane-modified polymers is achieved, and the evaluation of the performance of photovoltaic packaging materials is improved. and optimization capabilities.

CN119269325APending Publication Date: 2025-01-07CHANGZHOU SVECK PHOTOVOLTAIC NEW MATERIAL

Patent Information

Application Number
CN202411613765.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The prior art lacks effective methods to test the grafting rate of silane-grafted polyolefins, which affects the evaluation of silane modification and the performance optimization of photovoltaic packaging materials.

Method used

Using the TGA ash conversion method, the unreacted silane grafted polyolefin grafting material was placed in an organic solvent to extract and remove unreacted silane, and then calcined in TGA and calculate the relative grafting rate through elemental analysis to achieve silane grafting polyolefin Accurate measurement of grafting rate.

Benefits of technology

This method improves the testing efficiency and reliability of grafting rate, can truly reflect the graft stability in the production process, simplifies the operation process, and provides an accurate evaluation of the performance of silane-modified polymers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119269325A_ABST
    Figure CN119269325A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of photovoltaics, in particular to a method for testing the grafting rate of silane grafted polyolefin for a photovoltaic packaging adhesive film. Comprising the following steps: S1, extracting a silane grafted polyolefin grafting material in an organic solvent to remove unreacted silane or residual peroxide, washing for multiple times after extraction is completed, and drying for later use; and S2, weighing and recording the mass of the crucible and the extracted silane grafted polyolefin colloidal particles, then putting the crucible filled with the colloidal particles into TGA for calcination, weighing the total mass of the crucible and the sample after calcination is finished, and converting the relative grafting rate by using the ash content of the TGA. According to the invention, the grafting rate of silane grafted polyolefin can be timely and effectively tested and evaluated, so that the grafting stability in the grafting material production process can be truly reflected. Meanwhile, the grafting rate testing method is high in efficiency, simple and reliable to operate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photovoltaics, in particular to a method for testing the grafting rate of silane-grafted polyolefin for photovoltaic encapsulation adhesive films. Background Art

[0002] Ethylene-vinyl acetate copolymer (EVA) has good electrical and barrier properties and is widely used in electrical insulation, cable sheathing, packaging, packaging anti-corrosion and other fields. EVA is used as a packaging material in photovoltaic modules and has a high volume resistivity (0.2–1.4×10 16 Ωcm -1 ), high light transmittance (higher than 91%), high bonding strength to glass and high transparency. However, EVA has low tensile strength, and its thermal stability and UV stability limit its application, so it is necessary to modify traditional EVA.

[0003] At present, the main modification methods include blending, crosslinking and grafting. In fact, blending modification is easy to reduce the properties of polymers; radiation crosslinking is costly and complex; peroxide crosslinking and initiation grafting processes are easy to cause polymer degradation. Silane grafting crosslinking is an effective method recently developed to prepare EVA with high mechanical properties. The most commonly used silane is vinyl trimethoxy silane (VTMS), which is usually introduced into EVA by melt grafting using peroxide. In addition, vinyl trimethoxy silane coupling agent, with organic functional groups and inorganic Si-O-Si structure, usually has good compatibility with polymers and excellent thermal stability. Specifically, trioxy silane monomers (R-Si-(OR′)3) have two very different reaction sites. On the one hand, the R group is an organic group with a double bond that can be polymerized by free radical polymerization. The nature of this group will determine the free radical reactivity of the silane monomer, thereby determining the incorporation of the silane moiety into the polymer backbone. The second reaction site is the alkoxy group (OR′), which is responsible for improving performance. Alkoxy groups are usually small groups, such as methoxy or ethoxy, which are hydrolyzed to form silanol groups. After hydrolysis occurs, silanols can further react through condensation reactions. They can react with other silanol groups in different polymer chains to crosslink polymers, or they can react with OH groups present on the surface of substrates or inorganic particles to improve adhesion and compatibility with polymers. For example, An et al. prepared HMSPP by silane grafting initiated by in situ thermal induced reaction with improved thermal stability and tensile strength. The silane grafting reaction mechanism process is that the PP chain first breaks under high temperature shear field to form macromolecular free radicals, followed by the free radical grafting reaction of vinyl alkoxy silane on the PP chain to form silane grafted PP, and finally the silane grafted PP is crosslinked in hot water. The crosslinking reaction involves the hydrolysis of alkoxy groups and then the condensation of hydroxyl groups to form stable siloxane bonds.

[0004] However, there are few reports on the test method of grafting rate of polyolefin after grafting modification. Chinese patent CN117417370A discloses 3-glycidyl ether alkoxysilane modified EVA grafting monomer, and its monomer grafting rate is calculated by measuring the integral area of ​​the characteristic peak of the sample after acetone extraction treatment using a solid nuclear magnetic resonance spectrometer, but the position of the characteristic peak and the specific calculation formula are not described. On the other hand, although nuclear magnetic resonance has high resolution, it requires pure samples and less interference from additives. Chinese patent CN118725202A discloses a method for improving the grafting stability of initiator and maleic anhydride after dissolving them evenly and then mixing them with EVA. The grafting rate and melt index data results provided confirm the grafting stability, but the grafting rate test method used is not provided. Chinese patent CN 112730296A discloses a test method for calculating the hydroxyl grafting rate of kaolinite by testing the sample peak area using a method of fitting infrared absorption spectra. Although infrared can be used to quickly and accurately test and calculate the grafting rate, for unknown samples, the test results cannot be directly obtained.

[0005] Based on this, this patent will provide a method for converting the grafting rate of silane-grafted polyolefins through TGA ash content. Summary of the invention

[0006] The purpose of the present invention is to provide a method for testing the grafting rate of silane-grafted polyolefin for photovoltaic encapsulation film, so as to solve the above technical problems.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0008] A method for testing the grafting rate of silane-grafted polyolefin for photovoltaic encapsulation film, the testing method comprising the following steps:

[0009] S1: extracting the silane-grafted polyolefin grafted material in an organic solvent to remove unreacted silane or residual peroxide, washing it several times after the extraction is completed and drying it for later use;

[0010] S2 weighs and records the mass of the crucible and the extracted silane-grafted polyolefin particles, then places the crucible containing the particles in TGA for calcination. After calcination, weigh the total mass of the crucible and the sample, and use the TGA ash content to convert the relative grafting rate.

[0011] Furthermore, the organic solvent in step S1 is selected from one or more of acetone, ethyl acetate and xylene, and the extraction time is 1 to 24 hours.

[0012] Furthermore, after the extraction in step S1 is completed, anhydrous ethanol is used for washing.

[0013] Furthermore, the silane-grafted polyolefin graft material is a graft material whose raw materials include polyolefin, silane coupling agent and peroxide.

[0014] Furthermore, the polyolefin is selected from ethylene-vinyl acetate copolymer or ethylene-α-olefin copolymer elastomer.

[0015] Furthermore, the silane coupling agent is selected from one of vinyl trimethoxy silane, vinyl triethoxy silane, vinyl tri(β-methoxyethoxy) silane, r-aminopropyl triethoxy silane, and γ-methacryloxypropyl trimethoxy silane.

[0016] Furthermore, the peroxide is selected from one of tert-butyl peroxy-2-ethylhexyl carbonate, tert-amyl peroxy (2-ethylhexyl) carbonate, dibenzoyl peroxide, and dioctyl phthalate.

[0017] Furthermore, the ash content in step S2 is TGA residual mass. Through elemental analysis, it can be known that the ash content is SiO2. The conversion formula is: relative grafting rate = ash content / 0.4.

[0018] Beneficial Effects

[0019] In fact, adding peroxide to the polymer system can release water inside at high temperature, and the generated water hydrolyzes and crosslinks the silane. The reaction mechanism of silane grafted polyolefin is as follows: in the first step, EVA breaks under the free radicals initiated by peroxide to form macromolecular free radicals; in the second step, the free radical grafting reaction of vinyltrimethoxysilane forms silane grafted EVA on EVA. However, unreacted silane may still remain in the silane grafted polyolefin grafted material. Since silane is soluble in organic solvents, unreacted silane can be extracted and removed with organic solvents such as acetone, ethyl acetate, and xylene to facilitate testing the grafting rate of silane grafted polyolefin. The larger the ash value, the greater the grafting rate of silane grafted polyolefin. Based on this, the present invention can timely and effectively test and evaluate the grafting rate of silane grafted polyolefin, thereby truly reflecting the grafting stability in the production process of the grafted material. At the same time, the grafting rate test method based on this is efficient, easy to operate and reliable. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The grafting reaction mechanism diagram of silane grafted polyolefin is shown;

[0021] Figure 2 shows infrared spectra of vinyltrimethoxysilane, ethylene-vinyl acetate copolymer, and silane-grafted polyolefin;

[0022] Figure 3 The elemental analysis diagram of ash after calcination of Example 1 is shown;

[0023] Figure 4 The TGA graph of the silane grafted polyolefin in Example 1 is shown;

[0024] Figure 5 The TGA graph of the silane grafted polyolefin in Example 2 is shown;

[0025] Figure 6 The TGA graph of the silane grafted polyolefin in Example 3 is shown;

[0026] Figure 7 The TGA graph of the silane grafted polyolefin in Example 4 is shown;

[0027] Figure 8 The TGA graph of the silane grafted polyolefin in Example 5 is shown;

[0028] Fig. 9 The TGA graph of the silane grafted polyolefin in Example 6 is shown;

[0029] Fig.10 The TGA graph of the silane grafted polyolefin in Example 7 is shown. DETAILED DESCRIPTION

[0030] The present invention will now be described in further detail in conjunction with specific embodiments. The following embodiments may enable those skilled in the art to more fully understand the present invention, but these embodiments are not intended to limit the scope of protection of the present invention. "One embodiment" or "embodiment" referred to herein refers to a specific feature, structure or characteristic that may be included in at least one implementation of the present invention. "In one embodiment" appearing in different places in this specification does not refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.

[0031] Example 1

[0032] (1) Place the peroxide and silane coupling agent mixed in a certain proportion at the liquid feed port, and place EVA at the pellet discharge port. After melt mixing, drawing and pelletizing by a twin-screw extruder unit, grafted granulation is obtained. Two air drying systems ensure granulation drying. The control temperature of the twin-screw extruder from the feed barrel to the discharge barrel is set to 80°C, 190°C, 180°C, 160°C and 150°C in sequence, the screw speed is 180r / min, and the extrusion temperature is 250°C. The peroxide can be tert-butyl peroxide 2-ethylhexyl carbonate, tert-amyl peroxide (2-ethylhexyl) carbonate, dibenzoyl peroxide, dioctyl phthalate; the silane coupling agent can be vinyl trimethoxysilane, vinyl triethoxysilane, vinyl tri(β-methoxyethoxy) silane, r-aminopropyl triethoxysilane, γ-methacryloxypropyl trimethoxysilane, etc. The peroxide and silane coupling agent can be mixed in any combination.

[0033] (2) About 5 g of silane-grafted polyolefin particles were placed in 30 mL of acetone for extraction for 1 h. After the extraction was completed, they were washed several times with ethanol and dried for later use.

[0034] (3) Relative grafting rate calculated from TGA ash content

[0035] The relative grafting rate is calculated using the ash content. The ash content is the residual mass of TGA. Through elemental analysis, it is known that the ash content is SiO2. The conversion formula is relative grafting rate = ash content / 0.4.

[0036] Taking vinyl trimethoxy silane as an example, the silane coupling agent is:

[0037] Molar mass of vinyltrimethoxysilane (CH2=CHSi(OCH3)3):

[0038] Carbon (C): 12.01 g / mol × 2 = 24.02 g / mol, Hydrogen (H): 1.01 g / mol × 4 = 4.04 g / mol,

[0039] Silicon (Si): 28.09 g / mol, oxygen (O): 16.00 g / mol × 3 = 48.00 g / mol,

[0040] Methyl (CH3): 15.04 g / mol × 3 = 45.12 g / mol;

[0041] Total molar mass = 24.02 + 4.04 + 28.09 + 48.00 + 45.12 = 149.27 g / mol.

[0042] Number of moles of 1g vinyltrimethoxysilane:

[0043] Number of moles = mass / molar mass = 1 g / 149.27 g / mol ≈ 0.0067 mol;

[0044] According to the reaction equation:

[0045] CH2=CH-Si(OCH3)3→SiO2+CH2=CH2+3CH3OH

[0046] It is known that 1 mol of vinyltrimethoxysilane produces 1 mol of silicon dioxide;

[0047] Based on this, 0.0067 mol of vinyltrimethoxysilane generates 0.0067 mol of silica,

[0048] The molar mass of silicon dioxide = 28.09 g / mol (Si) + 16.00 g / mol × 2 (O) = 60.09 g / mol. The mass of silicon dioxide generated = number of moles × molar mass = 0.0067 mol × 60.09 g / mol ≈ 0.40 g. Therefore, 1 gram of vinyltrimethoxysilane decomposes at high temperature to generate about 0.40 grams of silicon dioxide.

[0049] Figure 1 The grafting reaction mechanism diagram of silane grafted polyolefin is shown. In the first step, EVA breaks down under the initiation of peroxide free radicals to form macromolecular free radicals; in the second step, the free radical grafting reaction of vinyltrimethoxysilane forms silane grafted EVA on EVA, forming a stable siloxane bond.

[0050] Figure 2 The infrared spectra of vinyl trimethoxysilane, ethylene-vinyl acetate copolymer and silane-grafted polyolefin are shown. It can be seen that compared with pure ethylene-vinyl acetate copolymer, the spectrum of ethylene-vinyl acetate copolymer has a peak at 1743 cm -1 There are typical absorption peaks related to C=O at 1257cm -1 The characteristic absorption peaks related to COC are located at 1372, 1465, 2862 and 2927 cm -1 The peaks at 1088 cm-1 are attributed to -CH3 symmetric bending vibration, -CH2 rocking vibration, and aliphatic -CH2 symmetric and asymmetric stretching vibration. In addition to all the above characteristic peaks, the silane grafted polyolefin has a peak at 1088 cm-1. -1 Additional peaks are also shown at , which are attributed to the Si-O-CH3 bond, proving that vinyltrimethoxysilane has been successfully grafted onto the EVA chain.

[0051] Figure 3 The elemental analysis chart of the ash after calcination of Example 1 is shown, indicating that the ash is composed of SiO2.

[0052] The grafting rate of Example 1 is 1.6, and the volume resistivity is 1.16*10 14 Ω*cm, the transmittance at 290-380nm is 89.540, and the transmittance at 380-1100nm is 92.625.

[0053] The TGA graph of silane grafted polyolefin in this embodiment is shown in FIG. Figure 4 .

[0054] Example 2

[0055] The difference from Example 1 is that (2) about 5 g of silane-grafted polyolefin particles were placed in 30 mL of acetone and extracted for 12 h.

[0056] The grafting rate of Example 2 is 1.28, and the volume resistivity is 2.24*10 14 Ω*cm, the transmittance at 290-380nm is 89.781, and the transmittance at 380-1100nm is 92.641.

[0057] The TGA graph of silane grafted polyolefin in this embodiment is shown in FIG. Figure 5 .

[0058] Example 3

[0059] The difference from Example 1 is that (2) about 5 g of silane-grafted polyolefin particles are placed in 30 mL of acetone and extracted for 24 h.

[0060] The grafting rate of Example 3 is 1.33, and the volume resistivity is 2.12*10 14 Ω*cm, the transmittance at 290-380nm is 89.804, and the transmittance at 380-1100nm is 92.623.

[0061] The TGA graph of silane grafted polyolefin in this embodiment is shown in FIG. Figure 6 .

[0062] Example 4

[0063] The difference from Example 1 is that (2) about 5 g of silane-grafted polyolefin particles were placed in 30 mL of ethyl acetate and extracted for 1 hour.

[0064] The grafting rate of Example 4 is 1.53, and the volume resistivity is 1.83*10 14 Ω*cm, the transmittance at 290-380nm is 89.702, and the transmittance at 380-1100nm is 92.631.

[0065] The TGA graph of silane grafted polyolefin in this embodiment is shown in FIG. Figure 7 .

[0066] Example 5

[0067] The difference from Example 1 is that (2) about 5 g of silane-grafted polyolefin particles were placed in 30 mL of xylene and extracted for 1 hour.

[0068] The grafting rate of Example 5 is 1.55, and the volume resistivity is 0.49*10 14 Ω*cm, the transmittance at 290-380nm is 89.533, and the transmittance at 380-1100nm is 92.637.

[0069] The TGA graph of silane grafted polyolefin in this embodiment is shown in FIG. Figure 8 .

[0070] Example 6

[0071] The difference from Example 1 is that the extrusion temperature in (1) is 195°C.

[0072] The grafting rate of Example 6 is 1.9, and the volume resistivity is 0.34*10 14 Ω*cm, the transmittance at 290-380nm is 89.850, and the transmittance at 380-1100nm is 92.670.

[0073] The TGA graph of silane grafted polyolefin in this embodiment is shown in FIG. Fig. 9 .

[0074] Example 7

[0075] The difference from Example 1 is that the screw speed in (1) is 145 rpm / min.

[0076] The grafting rate of Example 7 is 1.78, and the volume resistivity is 1.94*10 14 Ω*cm, the transmittance at 290-380nm is 89.590, and the transmittance at 380-1100nm is 92.574.

[0077] The TGA graph of silane grafted polyolefin in this embodiment is shown in FIG. Fig.10 .

[0078] Table 1 shows the grafting ratio, volume resistivity and light transmittance of the silane-grafted polyolefin in Examples 1 to 7 calculated based on TGA ash content.

[0079]

[0080]

[0081] Table 1

[0082] With the above embodiments of the present invention as inspiration, through the above description, relevant personnel in this field can make various changes and modifications without departing from the technical idea of ​​the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention. The technical scope of the present invention is not limited to the content of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A method for testing the grafting rate of silane-grafted polyolefin for photovoltaic encapsulation film, characterized in that: The test method comprises the following steps: S1. extracting the silane-grafted polyolefin grafted material in an organic solvent to remove unreacted silane or residual peroxide, washing it several times after the extraction is completed and drying it for later use; S2 Weigh and record the mass of the crucible and the extracted silane-grafted polyolefin particles, then place the crucible containing the particles in a TGA for calcination. After calcination, weigh the total mass of the crucible and the sample, and use the TGA ash content to convert the relative grafting rate.

2. The method for testing the grafting rate of silane-grafted polyolefin for photovoltaic encapsulation film according to claim 1, characterized in that: The organic solvent in step S1 is selected from one or more of acetone, ethyl acetate and xylene, and the extraction time is 1 to 24 hours.

3. The method for testing the grafting rate of silane-grafted polyolefin for photovoltaic encapsulation film according to claim 1, characterized in that: After the extraction in step S1 is completed, the extraction step is performed by washing with anhydrous ethanol.

4. The method for testing the grafting rate of silane-grafted polyolefin for photovoltaic encapsulation film according to claim 1, characterized in that: The silane-grafted polyolefin graft material is a graft material containing polyolefin, silane coupling agent and peroxide in the raw materials.

5. The method for testing the grafting rate of silane-grafted polyolefin for photovoltaic encapsulation film according to claim 4, characterized in that: The polyolefin is selected from ethylene-vinyl acetate copolymer or ethylene-α-olefin copolymer elastomer.

6. The method for testing the grafting rate of silane-grafted polyolefin for photovoltaic encapsulation film according to claim 4, characterized in that: The silane coupling agent is selected from one of vinyl trimethoxy silane, vinyl triethoxy silane, vinyl tri(β-methoxyethoxy) silane, r-aminopropyl triethoxy silane, and γ-methacryloxypropyl trimethoxy silane.

7. The method for testing the grafting rate of silane-grafted polyolefin for photovoltaic encapsulation film according to claim 4, characterized in that: The peroxide is selected from one of tert-butyl peroxy-2-ethylhexyl carbonate, tert-amyl peroxy-(2-ethylhexyl) carbonate, dibenzoyl peroxide, and dioctyl phthalate.

8. The method for testing the grafting rate of silane-grafted polyolefin for photovoltaic encapsulation film according to claim 1, characterized in that: The ash content in step S2 is the TGA residual mass. Through elemental analysis, it can be known that the ash content is SiO2. The conversion formula is: relative grafting rate = ash content / 0.4.

Citation Information

Patent Citations

  • Mid-infrared absorption spectrum-based kaolinite hydroxyl intercalation / grafting ratio testing method

    CN112730296A

  • EVA (ethylene-vinyl acetate) grafting monomer as well as preparation method and application thereof

    CN117417370A

  • Method for improving EVA (Ethylene Vinyl Acetate) grafting stability

    CN118725202A

Cited By

  • Yellowing-resistant offset printing LED tin printing ink and preparation method thereof

    CN119955348A

  • Method for detecting grafting rate of nano adsorption reducing imbibition agent based on infrared spectrum

    CN122567584A

  • Method for detecting grafting rate of nano-desorption and imbibition agent based on infrared spectrum

    CN122567584B